PENGARUH KUALITAS PRODUK, HARGA, PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN JAKET ARLINAX BULLS SYNDICATE DI SURAKARTA - Damayanti, Wika (Indonesian Journal of Strategic Management, 2021)
This research aims to find out the decision to purchase Arlinax Bulls Syndicate jacket in Surakarta which is influenced by several factors such as product quality, price, promotion and service. The data source in this study is primary and secondary data, primary data by disseminating questionnaires online to respondents, obtained a number of 100 respondents and secondary data used comes from company documents, books, research journals, the internet. To precisely uncover research data this study uses instrument data tests, classical assumption tests, and hypothesis tests. The data is processed statistically using SPSS (Statistical Package for Social Sciene). The output of the results shows that there is a significant influence on prices, services and promotions and insignificant to the quality of products in purchasing decisions.